The association between protective behavioral strategies and alcohol-related problems: An examination of race and gender differences among college drinkers. Issue 1 (2nd January 2016) - Clarke, Nickeisha; Kim, Su-Young; Ray, Anne E.; White, Helene R.; Jiao, Yang; Mun, Eun-Young
ABSTRACT: This study examined race and gender differences in use of specific types of protective behavioral strategies (PBS) and the moderating effects of race and gender on the relationship between PBS use and alcohol problems, controlling for alcohol use, among a large sample of Asian, Black, and White college drinkers. There were significant racial and gender differences in the types of PBS used. Moderation analyses indicated that PBS were more protective for women than men against experiencing alcohol-related problems. There were no significant race effects or race-by-gender interaction effects on alcohol problems. Implementing PBS may be beneficial for all college students.